Total navicular and cuboid replacement utilizing patient specific 3D printed implants for treatment of osteonecrosis of the midfoot: Case report and technique guide - John R. Constantino; Adam D. Perler (Annals of 3D Printed Medicine, 2024)
Osteonecrosis of the midfoot is a rare but debilitating pathology that can severely decrease quality of life. Surgical treatment is often complex and can lead to suboptimal outcomes. Additive manufacturing or 3D printing can provide a more patient specific approach to address these difficult entities. This case report highlights the successful use of custom 3D printed implants to replace the navicular and cuboid bones for treatment of osteonecrosis by providing a unique mixture of joint fusion and resurfacing interfaces in a 47-year-old active female. At the final follow up of 30 months, the patient continues to express satisfaction with her procedure and perform physical activities without pain.